Repeated sprint protocols with standardized versus self-selected recovery periods in elite youth soccer players: Can they pace themselves? A replication study - Engel, F. A.; Altmann, S.; Chtourou, H.; Woll, A.; Neumann, R.; Yona, T.; Sperlich, B. (Pediatric Exercise Science, 2022)
Purpose: Replicating the studies of Gibson et al and Brownstein et al to assess performance, and physiological, and perceived variables during a repeated sprint protocol (RSP) with standardized versus self-selected recovery in youth soccer players. Methods: Nineteen male soccer players (age 13.1 [1.3] y) completed 2 separate RSPs. RSP1: 10 × 30-m sprints with 30-second recovery and RSP2: 10 × 30-m sprints interspersed with self-selected recovery periods. Mean time of both 10 × 30-m RSPs and self-selected recovery periods of RSP2 were assessed. Heart rate, blood lactate concentration, and rates of perceived exertion were measured following RSPs. Results: RSP2 revealed longer recovery periods (RSP1: 30.0 [0.0] s; RSP2: 39.0 [7.7] s; P < .001; effect size d = 1.648) with shorter repeated sprint time (mean 30-m sprint time: RSP1: 4.965 [0.256] s; RSP2: 4.865 [0.227] s; P = .014; d = 0.414). Blood lactate concentration (P = .002-.005; d = 0.730-0.958), heart rate (P < .001; d = 1.353), and rates of perceived exertion (RSP1: 14.9 [1.9]; RSP2: 12.9 [2.1]; P = .016; d = 1.046) were higher following RSP1. Conclusion: In contrast to the original studies, the present replication study demonstrated that self-selected recovery periods during a RSP leads to better repeated sprint performance compared with standardized recovery periods in youth soccer players. The better repeated sprint performance with individual recovery durations in RSP2 was achieved with less physiological and perceived effort.